2009
DOI: 10.4102/pythagoras.v0i69.43
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the introduction of the equal sign in three Grade 1 textbooks

Abstract: This paper attempts to analyse how the concept of the equal sign is introduced to learners in Grade 1 textbooks in use in South Africa. In doing this, three Grade 1 textbooks (learner’s book and their accompanying teacher’s guide) were analysed in terms of the first appearance of the equal sign. Analysis reveals that the equal sign is introduced operationally and its introduction is subsumed in the introduction of the addition and subtraction signs. The author argues for the equal sign to be accorded equal sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…They regard the equal sign as a 'command' for executing the operation appearing on the right-hand side (Sfard, 1991). Many researchers (Bush & Karp, 2013;Essien, 2009;Essien & Setati, 2006;Hattikudur & Alibali, 2010;Jones et al, 2012;Stephens et al, 2013) have explored the interpretation of the equal sign as an invitation to an answer.…”
Section: Researcher: Okay But There Is -1 On the Right-hand Side Of mentioning
confidence: 99%
See 2 more Smart Citations
“…They regard the equal sign as a 'command' for executing the operation appearing on the right-hand side (Sfard, 1991). Many researchers (Bush & Karp, 2013;Essien, 2009;Essien & Setati, 2006;Hattikudur & Alibali, 2010;Jones et al, 2012;Stephens et al, 2013) have explored the interpretation of the equal sign as an invitation to an answer.…”
Section: Researcher: Okay But There Is -1 On the Right-hand Side Of mentioning
confidence: 99%
“…The textbooks contained little information for teachers to explain the equal sign to learners when teaching. Similarly, textbook explanations of the equal sign were studied in South Africa, where Essien (2009) found that textbooks introduced the equal sign operationally using addition and subtraction of numbers or expressions.…”
Section: Sources Of Learners' Operational Understandingmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather many learners at primary and early secondary levels understood the equal sign as either a do-something symbol that automatically invite them to write the answer and/or a unidirectional symbol. Essien (2009) though argues for the equal sign to be given the same status and attention as the addition and subtraction signs both in the textbooks and the curriculum. The Principles and Standards also notes that the common learners' understanding of the equal sign at this stage (foundation phase) should be more accurate than the limited understanding of the equal sign as signifying "the answer is coming".…”
Section: Literature Reviewmentioning
confidence: 99%
“…Pictorial and symbol illustrations on the chalkboard only followed the practical part at a later stage respectively. Essien (2009) argues that the equal sign should first be introduced using appropriate pictorial representations and artefacts before the introduction of the plus and minus signs. This was the strategy used meticulously by the teacher observed.…”
Section: Introductionmentioning
confidence: 99%